The implementation of innovative “Kantong Sholat” media to enhance students' learning motivation at integrated Islamic elementary schools - Hasriadi, Hasriadi; Sholehan , Shopiatus; Musdianti, Musdianti (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
The purpose of this study is to increase the motivation of class 2B SDIT Al Bashirah students to learn fiqh material about the pillars of prayer by using prayer bag media. As a result of monotonous conventional learning methods, students tend to be passive and unmotivated. Prayer bag media is an interactive tool that allows students to learn visually and practice directly about prayer movements. The Classroom Action Research (PTK) method, which is used in two cycles, uses the Kemmis and McTaggart model. After data was collected through documentation, interviews, and observations, qualitative descriptive analysis was used. The results showed that learners felt more motivated to learn after using the prayer bag media. In the pre-cycle, only 11% of learners showed excellent motivation, in cycle I it increased to 22% and 50% in cycle II. It is evident that the use of prayer bag media increases learners' engagement, enthusiasm and understanding of the material. This study suggests the use of innovative media in Islamic religious education to make education more interesting and effective.